Relationship Between Polycyclic Aromatic Hydrocarbons and Cardiovascular Diseases: A Systematic Review - Mallah, Manthar Ali; Mallah, Mukhtiar Ali; Liu, Yang; Xi, He; Wang, Wei; Feng, Feifei; Zhang, Qiao (Frontiers in Public Health, 2021)
Objective The primary aim of this systematic review was to examine the relationship of polycyclic aromatic hydrocarbon (PAH) exposure with cardiovascular diseases (CVDs) and elaborate the current knowledge and recent advances in the area of PAH and its effects on CVDs and discuss the growing epidemiological evidence linking PAH to CVDs on the health of human populations. In this systematic review, the increased risk of cardiovascular diseases and their relationship with PAHs were discussed in detail. Methods On 05th April 2021, a systematic literature search was conducted using PubMed/Medline and Web of Science search engines in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria. The search was limited to articles that were written in English and dealt with human issues. All original peer-review publications were considered for inclusion. Comments, case reports, reviews, duplicated papers, and conference reports were excluded. Data was collected from included papers by two independent reviewers. Results Conclusively, 20 research articles published between 2005 and 2021 were chosen for the final analysis. The systemic review included 20 studies with a variety of geographical studies. The most common research category among the nominated studies were time-series studies followed by retrospective cohort, cross-sectional, quasi-experimental, panel, and case-control studies. Most of the studies were conducted in the United States, whereas others were showed in various geographical countries around the world, such as Denmark, Germany, Finland, Netherlands, France, China, Norway, Korea, Sweden, Saudi Arabia, and Belgium. Eight studies assessed the association between PAH exposure and CVDs, four articles observed this relationship with blood pressure (BP), two observed association between atherosclerotic CVD and PAH, one congenital heart disease, cardiovascular events, and two with obesity. Furthermore, in some investigations, a favorable association between PAH exposure and hypertension as well as PAH exposure and obesity was found. Conclusion In conclusion, this systematic review examined the relationship of PAH exposure with CVDs and CVD-related risk factors by searching several digital databases. After a comprehensive literature searches and summarizing findings from 20 articles, the authors concluded that a positive relationship was observed between PAH exposure and CVD risks.